Enterprise Risk Management and Company’s Performance - Md. Jahidur Rahman; Sarmann I Kennedyd; Zhenkui Chen (Journal of Accounting, Business and Management (JABM), 2022)
The purpose of this study is to investigate the relationship between enterprise risk management (ERM) and company performance in the Chinese commercial industry. An enterprise risk management index was constructed from a strategic and operational point of view to assess the ERM level of Chinese commercial companies. ERM is also known as an integrated, comprehensive, and strategic management using the Simona-lulia (2014) approach. The study used a sample of 175 listed Chinese commercial companies from 2009 to 2018, and found that the imperfect ERM in the Chinese commercial industry as a whole had a negative effect on the performance of the companies. It also found that the size of the company, financial leverage, and intellectual capital can influence enterprise risk management. These results established a strong link between enterprise risk management and company performance in the Chinese commercial industry.